The role of dhimmis scholars in developing knowledge among Arabs in light of religious tolerance (Isaac as a model) (Journal of the College of Basic Education, 2019)
The message of Islam comes in the greatest universal religion those appeals to all mankind, which orders justice, forbids evil, and establishes the pillars of peace on earth. It is a message of tolerance, brotherhood and peaceful and human coexistence among all people regardless.Of their race, colors and beliefs in this tolerant human atmosphere, the non-Muslims lived side by side with their Muslim brothers to serve the society and raise its status, and contributed actively to the civilizational building, especially in the scientific field. As science develops nations, today we live in a brutal attack on Islam and Muslims. We need to appear the shining aspects of our Islamic civilization and clarify the role of non-Muslims in enriching them while working freely and connected to the land and feel citizenship, like other Muslims.Thus, we chose the family of Ishaq, Haneen ibn Ishaq, his sons Ishaq and Daoud, his nephew, and his student, Habish bin al-Hasan al-Asam, as an example of scientific creativity in the context of human coexistence. This innovation was in Baghdad the capital of the world and the beacon of science and crucifixion. We have a human civilization in its proper sense In this study, we mentioned the concept of the people of the first, and then we explained the nature of religious tolerance in Islam and its applications in the shadow of the Arab Islamic state, Then we talked about the (Isaac) as our model in this research, we played the role of nostalgia Ben Ishaq Abadi Christian in translation and transportation, especially through the currency as President of the House of Wisdom during the reign of the Caliph Al-Ma'mun (198 - 218 / 813-833m), as a new phase in the field The translation of many books of Greece from the Roman countries for the purpose of translation, as well as the emergence of a new way in the process of translation does not rely on the old literal translation was pioneered by Haneen ibn Ishaq, starting with the request of the Caliph to reform the previous translations and translate all the manuscripts of the Greeks, despite He was a young man at the time, but his scientific reputation was qualified him to deserve to be famous. He also stressed the importance of lunch and its nature in the treatment, and the medicines that depend on the plants in their manufacture, as the beginning of the new direction in the field of pharmacy, especially after the translation of medicine books to Greece from before nostalgia. Then we mentioned his death and what happened in the difference and the illusion of some historians.And then the search for the role of the sons of Haneen ibn Isaac and complement the role of their father in the field of translation and medicine, especially the role of his son Isaac, who was more distinguished than his brother David, and then we regret to mention the son of his sister and his student Habish bin Alasam explaining his role in completing the process of his uncle in the fields of medicine and translation.